Mitogenome phylogenetics: variation in topologies, divergence dates,and mutation rates among analysis partitions (2011)
Mitochondrial genomes are becoming more available thanks to recent technological advances in molecular biology. Its popularity as the tool of choice for phylogenetic analyses in a variety of taxa is increasing, and has resulted in improvement of overall results, as compared to traditional use of single mitochondrial markers such as the control region and CYTB. These differences in phylogenetic robustness provide incongruent conclusions among studies based on single mitochondrial markers and complete mitogenomes. Through detailed analysis of phylogenetic estimates from different genes we detected the most informative regions and the minimum amount of data necessary to reproduce mitogenomic-type results. We made use of two recently published complete mitogenome datasets of delphinids (Family Delphinidae) and killer whales (Orcinus orca) to compare phylogenetic estimation among individual genes and the mitogenome. Statistical comparative phylogenetics were employed to address differences in topologies, divergence dates and clock-like behavior among genes for both taxonomic groups. In both cases informative regions were coding genes and corresponded to less than a quarter of the complete mitogenome, yet these were not the same across both taxonomic groups, suggesting gene information content can depend on divergence time and taxonomy of the group studied. Although our results indicate that complete mitogenomes provide the most robust results, a minimum amount of data can be used when the complete sequence is unavailable, and previous studies based on single genes can benefit from the addition of a few more mitochondrial markers, producing topologies and date estimates closer to those obtained using the entire mitogenome.